ERS International Congress 2017: a peek of outstanding abstracts from the clinical assembly - Kahn, Nicolas; Herth, Felix (Journal of thoracic disease, 2017)
This review highlights a selection of abstracts from the 2017 ERS International Congress in Milan presented by the clinical assembly’s groups of interventional pulmonology, general practice and primary care and rehabilitation and chronic care. Attention is brought to the increasing burden of disease of COPD and end-stage emphysema patients in China. The considerable efforts of Chinese pulmonary centers to conduct multicenter, randomized and controlled trials, investigating the possibilities of bronchoscopic lung volume reduction is underlined in the review. Furthermore, the key objectives of asthma management are stressed. We point out presentations emphasizing on achieving good control of daily symptoms and reducing the risk of asthma exacerbations. The findings of a randomized clinical trial evaluating the role of oxygen supplementation in rehabilitation therapy of COPD patients are analyzed. Additionally, another randomized clinical trial researching the influence of whole body vibration training (WBVT) in long-term (>1 year) lung transplant patients are discussed.
Gesehen am 22.07.2018
Accepted for publication: Sep 22, 2017